Preparasi dan Karakterisasi PP (Polypropylene) Termodifikasi LLDPE (Linear Low Density Polyethylene) dengan Teknik Pencampuran Biasa - Khavilla, Vidya Putri; Wahyuni, Sri; Riyanto, Ari Fajar; Jumaeri, Jumaeri; Harjono, Harjono (Universitas Negeri Semarang, 2019)
Polymers or plastics are one of the important material and progress very quickly. The purpose of this research to modify PP with LLDPE by the usual mixing techniques to improve some of the mechanical properties of PP. The quantity of LLDPE added to PP varies in 1%, 5%, 10%, 15%, and 20%. This research also studied the properties of LLDPE/PP with the addition of silica fume. Mixing LLDPE/PP is using the Extruder Pelletizing Twin Screw Lien Chiny and mixing LLDPE/PP-Silica using the injection molding method. LLDPE/PP was tested the mechanical properties and the results are as follows: MFR test of 8.36 g/cm3, the impact strength 3.3582 kg/cm2, tensile strength of 361.599 kgf/cm2, the flexural test of 52.1 MPa, hardness 108.2 Rscale, and density of 2.8441 g/cm3. LLDPE/PP-Silica tested mechanical properties by testing the impact strength and tensile strength. The physical characteristics of LLDPE/PP and LLDPE/PP-Silica analyzed using FTIR and SEM give the results of the functional group Si-O-Si and the agglomeration of silica on the morphology of LLDPE/PP-Silica. From all the results of the mechanical test it can be concluded that LLDPE/PP 10% has the results that are considered optimum because the value of the impact strength is best from the other variations. The LLDPE/PP-Silica is not increased mechanical properties compared to LLDPE/PP. Polymers or plastics are one of the important material and progress very quickly. The purpose of this research to modify PP with LLDPE by the usual mixing techniques to improve some of the mechanical properties of PP. The quantity of LLDPE added to PP varies in 1%, 5%, 10%, 15%, and 20%. This research also studied the properties of LLDPE/PP with the addition of silica fume. Mixing LLDPE/PP is using the Extruder Pelletizing Twin Screw Lien Chiny and mixing LLDPE/PP-Silica using the injection molding method. LLDPE/PP was tested the mechanical properties and the results are as follows: MFR test of 8.36 g/cm3, the impact strength 3.3582 kg/cm2, tensile strength of 361.599 kgf/cm2, the flexural test of 52.1 MPa, hardness 108.2 Rscale, and density of 2.8441 g/cm3. LLDPE/PP-Silica tested mechanical properties by testing the impact strength and tensile strength. The physical characteristics of LLDPE/PP and LLDPE/PP-Silica analyzed using FTIR and SEM give the results of the functional group Si-O-Si and the agglomeration of silica on the morphology of LLDPE/PP-Silica. From all the results of the mechanical test it can be concluded that LLDPE/PP 10% has the results that are considered optimum because the value of the impact strength is best from the other variations. The LLDPE/PP-Silica is not increased mechanical properties compared to LLDPE/PP.